ISOLATION OF AN OPHIDIAN PARAMYXOVIRUS (OPMV) IN A CAPTIVE RATTLESNAKE (Crotalus durissus terrificus) FROM BOTUCATU, SÃO PAULO STATE, BRAZIL - Nogueira, M. F. [UNESP]; Barrella, T. H. [UNESP]; Silva, R. J. Da [UNESP]; Lopes, C. A. M. [UNESP]; Araújo Júnior, J. P. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2002)
This study reports the isolation of an Ophidian Paramyxovirus (OPMV) in sputum of a captive rattlesnake (Crotalus durissus terrificus) kept in a serpentarium located in Botucatu, São Paulo State, Brazil. Polymerase chain reaction (PCR) and nested-PCR were performed for the identification of the isolated virus.
Keywords: Crotalus durissus terrificus; rattlesnake; Paramyxovirus; Ophidian Paramyxovirus; hemagglutination; polymerase chain reaction